O sagrado na adesão ao tratamento: significados atribuídos por pessoas vivendo com HIV/Aids - Costa, Dalva Aparecida Marques da (2014)
Despite the efforts to control Aids in the last years, through preventing methods and drug therapy, the adherence keep on being a challenge (BRASIL, 2013; ONU, 2010; BRASIL, 2007). In light of the foregoing, the following question was raised: What's the meaning of the sacred in the HIV/Aids treatment and its relation to the adherence to TARV? The objective was to understand the meaning of the sacred, here considered in a bigger sense, as something that is indeed important, attributed by people living with HIV/Aids in the treatment adherence process. To understand the reality to be investigated, it was adopted the ethnographic method, being this study carried out in an ONG in Goiânia that develops supporting groups to help people with HIV/Aids. Six people with HIV/Aids participated in the study. The data was acquired through interviews, participant observation, photos and field diary, in weekly meetings in the workshops. This material was organized and afterwards analyzed according to the content analyzis technique thematic modality. From the data analysis, two thematic categories were raised that are associated to these meanings: the meaning of the sacred in the control mechanisms in the treatment adherence and the meaning of the sacred in the supporting groups in the treatment adherence. The results made us understand that the treatment adherence is multifaceted and that the many meanings built by the PVHA are associated to the subjectivity of the sacred, that is, they are based on their specificities and sigularities. We believe that our findings can support an assistance process that consider the meanings of living with HIV/Aids, according to the percpectives of people who live this condition. We consider this recognition decisive to an effective treatment adherence because it opens up possibilities of dialogue and negotiation with people and collaborates in the public policies outlining.